EFISIENSI PRODUKSI USAHATANI KELAPA DALAM (Cocos nucifera Linn) DI KECAMATAN GAUNG ANAK SERKA KABUPATEN INDRAGIRI HILIR - Sisca Vaulina; Khairizal Khairizal; Hajry Arief Wahyudy (Jurnal Agribisnis Indonesia, 2018)
Efficiency in a farming process has a very important meaning in efforts to increase income of coconut farmers, especially in planning or developing coconut products that are effective and efficient in producing coconut. The purpose of this research is to analyze technical efficiency, allocative/price and economical of coconut plantation in Gaung Anak Serka Sub-district, Indragiri Hilir Regency. This research uses survey method. The research was conducted in Kecamatan Gaung Anak Serka (GAS), in four villages namely (1) Rambaian village; (2) Idaman village; (3) Iliran Village; (4) Tanjung Harapan village. Total samples were 62 farmers. The study was conducted in May 2017 until December 2017. Data analysis using software Frontier Version 4.1 C. The results showed that the average technical efficiency level achieved was 72.94 percent of maximum productivity. This shows that the farming coconut in Gaung Anak Serka Sub-district has been efficient to technical efficiency, but not yet allocatively/price and economical efficiency. The average value of the overall allocative efficiency is 2.40 and not economically efficient because the economic efficiency value obtained is 1.75.